PENGENALAN WARNA DAN BILANGAN MENGGUNAKAN MEDIA CAT AIR TERHADAP KECERDASAN KOGNITIF ANAK USIA 4 HINGGA 5 TAHUN - Sugito Muzaqi; Siti Nurhidayati (Universitas Narotama, 2021)
PAUD learning today must be fun and memorable for children, especially at the age of 4-5 years, children are able to recognize colors and symbols of numbers 1-10. However, at this age there are still those who cannot distinguish colors and call number symbols as the basis for learning for children. Due to monotonous learning using children's worksheets, making children bored and not understanding colors and numbers, therefore the researchers took the title